HISTORY OF ENERGY IN MEXICO - Russell, Philip L. Link ([S.l.])
1 online resource
Keywords: This volume synthesizes energy history in Mexico from pre-Conquest times to the present. It traces human development from a low-energy, sustainable existence to fossil fuel-based non-sustainability.The book familiarizes readers with different energy sources, what the advantages and disadvantages of each source are, and how the importance of each energy source has changed over time. From early agricultural beginnings and Spanish-introduced energy innovations to the rise of coal and oil, the volume analyzes how evolving energy sources produced sweeping environmental and social change. It also studies economic history from the approach of the emerging field of biophysical economics, recognizing the often-overlooked role of energy in Mexico's development. Linking this development to climate change, the book discusses the ways in which Mexico and the Global South are impacted by this crisis, despite doing little to cause climate change themselves. Later chapters inform readers of how energy issues have shaped U.S.-Mexican relations throughout the twentieth century and into today.A History of Energy in Mexico will be of value to students of environmental, economic, and Mexican history as well as political scientists, economists, and anthropologists.